Novel forms of reluctance among suspected child sexual abuse victims in adolescence - Nogalska, Agnieszka M. (Child maltreatment, 2023)
Adolescents tend to be neglected in research examining child sexual abuse (CSA) interviews, yet are often said to be particularly reluctant. This study examined reluctance among 119 10- to 17-year-old females questioned about suspected CSA (n = 25,942 responses), utilizing a scheme identifying previously overlooked types of reluctance in commercially sexually exploited (CSE) youth. In contrast to the CSE youth in a prior study, in which 26% of responses were reluctant, only 8% of CSA victims? responses expressed reluctance. Reluctance was unrelated to age, abuse characteristics, and don?t know (IDK) responding. Greater reluctance (but not IDK responding) was related to disclosure of fewer characteristics of abuse. Virtually all youth (93%) had disclosed prior to the interview, in contrast to previous studies examining reluctance among adolescent victims of internet-initiated sexual abuse and CSE. The way in which abuse is discovered may better explain reluctance than the age of the alleged victims.